Papillary Fibroelastoma of the Ascending Aorta - Karim M. Al-Azizi MD; Mohanad Hamandi MD; Ronald Baxter MD; Anita Krueger MD; Alexander W. Crawford BS; Michael William MD; Christopher Good DO; Nicolas Mead DO (SAGE Publishing, 2019)
Papillary fibroelastomas are rare benign primary cardiac tumors. They are typically found on valvular surfaces, most commonly, the aortic valve. In this article, we report a case of papillary fibroelastoma arising from the sinotubular junction of the ascending aorta, a rare and unusual site causing an embolic stroke.